Anti-inflammatory effect of interleukin-6 highly enriched in secretome of two clinically relevant sources of mesenchymal stromal cells - Dedier, Marianne; Magne, Brice; Nivet, Muriel; Banzet, Sébastien; Trouillas, Marina (Frontiers in Cell and Developmental Biology, 2023)
Despite several advances in the field of regenerative medicine, clinical management of extensive skin wounds or burns remains a major therapeutic issue. During the past few years, Mesenchymal Stromal Cells (MSCs) have emerged as a novel therapeutic tool to promote tissue repair through their anti-inflammatory, pro-trophic and pro-remodeling effects. They exert their biological activity mainly via the secretion of soluble bioactive molecules such as cytokines, growth factors, proteins and microRNAs which can be encapsulated within extracellular vesicles (EV). The recent discovery of their high plasticity to external stimuli has fostered the development of new targeted therapies known as priming strategies, to enhance their potential. Our team recently showed that Interleukin-1β (IL-1β)-primed gingival MSCs promote wound healing and epidermal engraftment in vitro, and in vivo through their secreted products that contain extracellular vesicles. In the present work, we investigated whether two common sources of MSCs, gingiva and bone marrow, could respond similarly to IL-1β to favor pro-healing capabilities of their secretome. We showed that both primed-MSC sources, or their related secreted products, are able to reduce inflammation in LPS-challenged human monocytic THP-1 cell line. IL-1β priming enhanced MSC secretion of wound healing-related growth factors, cytokines and miRNAs in both sources. Among them, interleukin 6 was shown to be involved in the anti-inflammatory effect of MSC secreted products. Overall, these results underline the pro-healing properties of both MSC sources and their secretome upon IL-1β priming and their potential to improve the current medical treatment of severe wounds.